Consumers' purchase behavior in Bangladesh: green products perspectives - Uddin, Burhan (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: This study aimed to identify the influential aspects of consumers' purchase behavior of green products perspectives in Bangladesh. Research methodology: The study was quantitative in nature. The main methodology chosen for this study was the questionnaire survey method (online survey). Primary data were gained through a structured questionnaire survey from 324 Bangladeshi respondents using a seven-point Likert scale from strongly disagree to strongly agree. Data were analyzed by statistical package for social science (SPSS) 25.0. Results: The study results found all the variables are significant with Consumers' green purchase behavior in Bangladesh. As the interpretation of descriptive and regression analyses, Environmental consciousness is the most influential factor in Consumers' green purchase behavior in Bangladesh. Other independent variables like Environmental Responsibility, Environmental Knowledge, Product Quality, Environmental Protection, Social Appeal, Green Advertisement also have positive & significant influences respectively. Limitation: The research was conducted & focused on Bangladesh only, so the study result may not be applicable in any other geographical location. The study was also limited by the sample size of 324 which is not representative of all customers in Bangladesh. There may have other variables except for the variables that are measured in this research. Contribution: The result and analyses of the study will be supportive for the researchers, government, marketing specialist, and business people to gain an insight into Consumers' green buying behavior in Bangladesh and direct them to find out other significant factors related to Consumers' green purchase behavior so that they can formulate their strategies & policies regarding environmental and consumption issues. Keywords: Green product, Green purchase, Consumer behavior, Sustainable product, Environmentally friendly, Green marketing